KETERLIBATAN GURU AQIDAH AKHLAK DALAM PEMBINAAN KEPRIBADIAN SISWA DI MTs AMAL SHALEH MEDAN TUNTUNGAN - Rosnani Rosnani (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2017)
Abstrak: The purpose of this study is to determine the involvement of teachers Akidah Akhlak inthe development of student personality, the program applied teachers Akidah Akhlak in the developmentof student personality, the forms of activities that teachers do Akhlak Akhlak in guidancepersonality students, constraints faced by teachers Akidah Akhlak in the development of studentpersonality , And know the efforts of teachers Akidah Akhlak overcome the barrier of studentpersonality development in MTs Amal Shaleh Medan Tuntungan.This research is using qualitativeresearch methods in order to reveal in depth data and facts about the implementation of learningAkidah Akhlak in coaching student personality in MTs Swasta Amal Shaleh Medan Tuntungan.Data collection techniques using interviews, observation, and document review. Then the data isanalyzed by data reduction step, data exposure, and conclusion. In this case the data is checkedwith techniques of credibility, dependability, komfirmabilitas, and transferability. The result ofthis research are (1) Involvement of Akidah Akhlak teacher in the development of student personalityin MTs Amal Shaleh Medan Tuntungan that is teacher as mentor or guidance to students, forexample or role model, and teacher as motivator for students in madrasah. (2) The teacher’seffort in the development of student personality in MTs Swasta Amal Shaleh Medan Tuntungan isby instilling the values of the faith to the students, guiding the students to implement the practiceof religion, familiarizing the behavior of religious worship practice, and supervising the studentsbehavior. (3) The form of student coaching personality control activities conducted at MTs SwastaAmal Shaleh Medan Tuntungan is to foster student behavior toward God. Foster student perilkauagainst fellow human beings, and foster behavior towards the environment. (4) Obstacles faced indeveloping student personality are the lack of awareness of students to implement the behavior ofreligious teachings and bad environmental influences cause students not to practice religion. (5)Overcoming obstacles is to give understanding to students that a good personality, invites to allparents to pay attention to students at home.